1998
DOI: 10.1046/j.1365-2052.1998.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β‐defensin prepropeptide mRNA from chicken and turkey bone marrow

Abstract: Four avian beta-defension prepropeptide cDNA sequences [gallinacins: Gal 1 (synonym CHP 1, chicken heterophil peptide 1), and Gal 2; turkey heterophil peptides: THP 1 and THP 2] were amplified from chicken or turkey bone marrow mRNA samples, respectively. Partial chicken beta-defensin cDNA sequences were obtained using degenerate primers based on chicken peptide sequences (Gal 1/CHP 1 and Gal 2). The complete cDNA sequences of the chicken beta-defensins were then determined by designing specific intrapeptidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…While defensins are often very prominent in granulocytes, they are not ubiquitous, since the neutrophils of mice (6), pigs (19), and horses (5) lack any defensins at all. Although avian ␤-defensins have been observed in bone marrow cells (4,7,15,16), neither their induction during infection nor their expression in epithelial cells has been reported until now.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While defensins are often very prominent in granulocytes, they are not ubiquitous, since the neutrophils of mice (6), pigs (19), and horses (5) lack any defensins at all. Although avian ␤-defensins have been observed in bone marrow cells (4,7,15,16), neither their induction during infection nor their expression in epithelial cells has been reported until now.…”
mentioning
confidence: 99%
“…␣-Defensins are remarkably abundant in human, rabbit, and rat neutrophils (20), but only ␤-defensins (at least 13 different isoforms) appear in the neutrophils of cattle (33). ␤-Defensins also occur in the polymorphonucleated granulocytes (heterophils) of chickens and turkeys (4,7,15,16). While defensins are often very prominent in granulocytes, they are not ubiquitous, since the neutrophils of mice (6), pigs (19), and horses (5) lack any defensins at all.…”
mentioning
confidence: 99%
“…Cells and tissues synthesizing antimicrobial peptides are generally those exposed to microbial pathogens. In the chicken, four ␤-defensins have been identified in heterophils (5,8), and a fifth defensin-like antimicrobial peptide, gallinacin 3, is expressed in a number of avian tissues (28). To date, however, no cationic antimicrobial peptides have been identified in the chicken small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important, as birds are universally recognized as a major reservoir of human enteropathogens but are themselves often asymptomatic. To date, four antimicrobial peptides, termed gallinacin 1 and 2 and turkey heterophil peptides 1 and 2, have been characterized from avian heterophils (5,8). All are homologous to ␤-defensins and show activity against Salmonella enteritidis and Campylobacter jejuni.…”
mentioning
confidence: 99%
“…Comparison of the mammalian and chicken TLR repertoires ed in classical mammalian defensins, which is thought to inactivate the positively-charged mature sequence allowing their storage in granules. Its absence in chicken defensins suggested that the chicken uses some other mechanism to neutralize the positive charges of the gallinacins whilst they are stored in granules (Brockus et al, 1998). In 2001, an epithelial ␤ -defensin named gallinacin 3, expressed in epithelial organs such as the lungs, bursa and intestine, was also characterised (Zhao et al, 2001).…”
Section: Defensinsmentioning
confidence: 99%